The Horned Frog - Ramlah, Zainudin; Elvy Quatrin, Deka; Nur Amirah, Md Sungif; Marly, Agoh; Sharizzaty, Mohd Rais; Muhammad Fadzil, Amram; Marius Joscha, Maiwald; Aida Shafreena, Ahmad Puad; Ahmad Hata, Rasit; Mohd Azlan, Jayasilan (Natural History Publication and in association with Universiti Malaysia Sarawak, 2015)
Ramlah Zainudin, Elvy Quatrin Deka, Nur Amirah Md Sungif, Marly Agoh, Sharizzaty Mohd Rais, Muhammad Fadzil Amram, Marius Joscha Maiwald, Aida Safreena Ahmad Puad, Ahmad Hata Rasit and Mohd-Azlan Jayasilan